Study of energy transfer mechanism in the Eu III and Gd III homobimetallic complexes containing the anti-inflammatory drug naproxen and N,N-donors ligands - Gomes, Emmanuel M.; Franco, Douglas F. [UNESP]; Scarpari, Sérgio L. [UNESP]; Colaço, Marcos V.; Ferreira, Monica S.; Freire, Ricardo O.; Marques, Lippy F. (Elsevier, 2019)
In this work, we present the synthesis, solid state characterization and complete photoluminescence study of new important homobimetallic lanthanide complexes containing the non-steroidal anti-inflammatory drug (NSAID) naproxen. The analytical and spectroscopic techniques reveals the formation of eight compounds of general formula [Ln 2 (nap) 6 (H 2 O) 4 ] (Eu 1 and Gd 2), [Ln 2 (nap) 6 (bpy) 2 ] (Eu 3 and Gd 4), [Ln 2 (nap) 6 (4,4'-dmbpy) 2 ] (Eu 5 and Gd 6) and [Ln 2 (nap) 6 (phen) 2 ] (Eu 7 and Gd 8), where: nap = naproxen ligand, bpy =2,2'-bipyridine, 4,4'-dmbpy = 4,4'-dimethyl-2,2'-bipyridine and phen = 1,10-phenanthroline. Using the RM1 model, the molecular structures of the Eu III complexes were calculated, with your optimized ground state geometries used to obtain all details involved in the energy transfer process. From the respective Gd III complexes were obtained the lowest ligand triplet states, proving that the photoluminescence in the Eu III naproxen complexes is proposed to be a ligand sensitized luminescence process. On the other hand, the position of the triplet states also explains the non-effective energy transfer in the Tb III naproxen complexes. The presence of N,N-donors ligands (bpy, 4,4'-dmbpy and phen) results in an 3–4-fold increase in the quantum efficiency when compared with the Eu III complex without nitrogen ligands. The high values of emission quantum efficiency (η ~ 70 - 98%) show the Eu III complexes can be potential candidates as emitters in biologic assays.
Keywords: Lanthanides; Luminescence; Naproxen; Photophysical properties